Pengaruh Pengendalian Internal, Kompetensi Perangkat Desa, dan Employee Productivity Terhadap Akuntabilitas Pengelolaan Dana Desa Dengan Budaya Organisasi Sebagai Variavel Moderasi - Indah Qothrun Nada Nada; Nanda Wahyu Indah Kirana (Yayasan Literasi Ilmiah Indonesia, 2025)
Purpose: This study aims to analyze the influence of internal control, village apparatus competence, and employee productivity on accountability in village fund management, with organizational culture as a moderating variable. Method: This study used a quantitative explanatory approach with a saturated sampling technique involving 107 village apparatus from 13 villages in Ujungpangkah District. Data were collected using a closed-ended questionnaire and analyzed using SmartPLS through outer and inner model testing. Finding: he results indicate that internal control and competence have a significant effect on accountability, while employee productivity does not. Furthermore, organizational culture strengthens the influence of internal control and employee productivity but does not moderate competence. Novelty: This study contributes by introducing employee productivity as an independent variable in the accountability model of village fund management, offering a new perspective that has rarely been examined in previous research.